Role of Anion Gap as a Prognostic Indicator in Acute Coronary Syndrome (ACS) - Nandita Sharma1, Anuj Varma2 , Sourya Acharya3 , Samarth Shukla4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Cardiovascular diseases are the leading cause of mortality in India and acute coronarysyndrome (ACS) is one of its anomalies, affecting mainly the coronary arterial blood supply and further thefunctioning of heart muscle. Its subtypes are Non-ST elevation myocardial infarction (NSTEMI), unstableangina, and ST-elevation myocardial infarction (STEMI). There are various diagnostic tools available todetect ACS like; electrocardiography (ECG), Cardiac stress test, Coronary CT angiography, Coronaryangiogram and cardiac biomarkers. Yet, tools for assessment of prognosis are scanty and new prognostictools are always welcomed, one such is anion gap, which can be detected by assessment of certain ionspresent in the serum, urine or plasma, etc. In this study we will assess the role of anion gap, in the assessmentof prognosis in ACS.Objective:1. To estimate anion gap (AG) in cases of acute coronary syndrome (ACS) at the time of diagnosis;2. To evaluate association of anion gap (AG) with the prognosis of acute coronary syndrome (ACS)Methodology: The study will be conducted in the Department of Medicine of a Rural Tertiary CareHospital. Estimation of anion gap (AG) in cases of acute coronary syndrome (ACS) will be evaluated at thetime of admission and after five days of treatment. Anion gap will be calculated or measured as differencebetween measured cations (Na+ + K+) and the measured anions (Cl- + HCO3-) in serum. Any complicationsduring the management will be noted (Heart failure arrhythmias, Hypotension, Reinfarction, Death) will becorrelated with anion gap (AG). Chi square test will be applied to evaluate statistical difference betweenamong anion group quartile groups.Results: The study will play a key role in identifying and assessing various other prognostic tools like aniongap, in assessing the severity of disease to some extent in patients with acute coronary syndrome.Conclusion: High value of serum anion gap levels is associated with poorer prognosis of the disease outcomein patients with acute coronary syndrome.